Fluor wins Al-Zour contracts in Kuwait. Issue 10 (October 2015) - Unknown
Abstract : Kuwait National Petroleum Co (KNPC) has selected a Fluor Corp-led joint venture team as the preferred bidder for two engineering, procurement and construction (EPC) packages.